Diatom-Derived Polyunsaturated Aldehydes Are Unlikely to Influence the Microbiota Composition of Laboratory-Cultured Diatoms - Chloe L. Eastabrook; Paul Whitworth; Georgina Robinson; Gary S. Caldwell (Life, 2020)
Diatom-derived oxylipins, including polyunsaturated aldehydes (PUA), are considered to have infochemical, allelochemical and bacteriostatic properties, with plausible roles as grazing deterrents and regulators of inter- and intraspecific competition. However, the extent and mechanisms of how PUA influence diatom−bacteria interactions remain unresolved. In this study, impacts on the diversity of the associated bacterial communities (microbiota) of two contrasting Skeletonema marinoi strains (a PUA and a non-PUA producer) were investigated under three nitrate conditions in batch culture. Further, the response of the culture microbiota was studied when spiked with PUA at ecologically relevant concentrations (86nM octadienal and 290nM heptadienal). Of the 741 identified OTUs, Proteobacteria was the most abundant phylum (62.10%), followed by Bacteroidetes (12.33%) and Firmicutes (6.11%). Escherichia/Shigella were the most abundant genera for all treatments. Similar communities were present in both spiked and non-spiked cultures suggesting they can tolerate PUA exposure at realistic concentrations. This study suggests that PUA are not major drivers of diatom−bacteria interactions in laboratory cultures.